2002
DOI: 10.1590/s1516-35982002000700014
|View full text |Cite
|
Sign up to set email alerts
|

Dias ao Parto de Fêmeas Nelore de um Experimento de Seleção para Crescimento: I - Modelo de Repetibilidade

Abstract: RESUMO -Registros de datas de entrada na monta e respectiva data do parto, referentes a 1.247 fêmeas Nelore dos rebanhos experimentais da Estação Experimental de Zootecnia de Sertãozinho (IZ -SP), selecionadas para altos (seleção e tradicional) e para médios (controle) pesos ao sobreano foram usados para obter a variável dias ao parto, a fim de estudar o efeito da seleção para crescimento sobre o desempenho reprodutivo. Arquivos de novilhas e de vacas e novilhas foram analisados incluindo e não incluindo as nã… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
5
1
1

Year Published

2002
2002
2018
2018

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 23 publications
2
5
1
1
Order By: Relevance
“…The Canchim SC12 and W12 means in our study agreed with those previously reported for the same Canchim herd (Gianlorenço et al, 2003;Talhari et al, 2003) and the DC HC , DC PHC , DFC and DFC P means were similar to values reported for Nelore beef cattle (Pereira et al, 2001;Mercadante et al, 2002;Forni and Albuquerque, 2005). Furthermore, the WC mean in our study was similar to that reported for ½ Canchim + ½ Nelore females (Alencar et al, 1999) and the WBS mean was only a little higher than that reported for Nelore cattle (Mercadante et al, 2004).…”
Section: Resultssupporting
confidence: 91%
See 3 more Smart Citations
“…The Canchim SC12 and W12 means in our study agreed with those previously reported for the same Canchim herd (Gianlorenço et al, 2003;Talhari et al, 2003) and the DC HC , DC PHC , DFC and DFC P means were similar to values reported for Nelore beef cattle (Pereira et al, 2001;Mercadante et al, 2002;Forni and Albuquerque, 2005). Furthermore, the WC mean in our study was similar to that reported for ½ Canchim + ½ Nelore females (Alencar et al, 1999) and the WBS mean was only a little higher than that reported for Nelore cattle (Mercadante et al, 2004).…”
Section: Resultssupporting
confidence: 91%
“…We also found that the model 1 DC estimated heritability calculated without penalized data, was low at h 2 = 0.04 for cows only and h 2 = 0.05 for heifers plus cows (Table 2) and similar to the lower limit (h 2 = 0.02 to h 2 = 0.09) of the heritability estimates reported by Mercadante et al (2002) and Forni et al (2003) using models which included permanent environmental effects. Furthermore, our model 2 DC P heritability estimates using penalized data were also low at h 2 = 0.03 for cows only and h 2 = 0.05 for heifers plus cows (Table 2) and were lower than the h 2 = 0.07 to h 2 = 0.16 reported by other workers (Meyer et al, 1991;Johnston and Bunter, 1996;.…”
Section: Resultssupporting
confidence: 84%
See 2 more Smart Citations
“…No ano anterior, as novilhas no período pré-acasalamento, com idade de 18 aos 24 meses, passaram por um longo período seco, com déficit pluviométrico anual de 50%, o que pode ter comprometido o ganho de peso e o desempenho reprodutivo futuro. Mercadante et al (2002), em um rebanho considerado controle, observaram, em maior disponibilidade de forragem, embora sem diferença estatística (P>0,05), menor DPP que o determinado em um rebanho considerado seleção (328 ± 2 x 333 ± 1 dias, respectivamente).…”
Section: Resultsunclassified